2022
DOI: 10.3390/micro2010014
|View full text |Cite
|
Sign up to set email alerts
|

Clove Essential Oil–Hydroxypropyl-β-Cyclodextrin Inclusion Complexes: Preparation, Characterization and Incorporation in Biodegradable Chitosan Films

Abstract: The encapsulation of clove essential oil (CEO) in hydroxypropyl-β-cyclodextrin (HP-β-CD) and the subsequent incorporation of the inclusion complex in an elastic chitosan film in order to achieve a controlled release profile of the volatile CEO are herein presented. Freshly distilled CEO was found to contain eugenol in concentrations higher than 70%. The kneading method was implemented for the preparation of a CEO-HP-β-CD inclusion complex, resulting in a 50% inclusion efficiency of the essential oil in particl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…CS−AITC coating in combination with organic acid application notably suppressed the colony growth rate of Salmonella enterica inoculated in grape tomato [ 25 ]. Furthermore, previous studies also suggested that adding bioactive compound and CD composed inclusion complex to the CS film−forming solution is beneficial to endow the pure film with enhanced functional and physical attributes [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…CS−AITC coating in combination with organic acid application notably suppressed the colony growth rate of Salmonella enterica inoculated in grape tomato [ 25 ]. Furthermore, previous studies also suggested that adding bioactive compound and CD composed inclusion complex to the CS film−forming solution is beneficial to endow the pure film with enhanced functional and physical attributes [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…This indicates a greater entrapment of HEO molecules by the hollow cavities of host molecules. In the traditionally used kneading methods, an extended duration of operation is typically required to achieve a more thorough dispersion of HEO molecules [ 23 , 24 ]. This dispersion is necessary for the molecules to effectively penetrate the cavities of host molecules.…”
Section: Resultsmentioning
confidence: 99%
“…Hădărugă et al [ 23 ] performed a 30 min of kneading process for the complexation of Danube common nase oil with β-CD and 2-HP-β-CD and reported a recovery yield of merely 77.7% and 79.9%. In a recent study reported by Adjali et al [ 24 ], clove essential oil was complexed with 2-HP-β-CD via the kneading method for 50 min, but the embedding fraction of clove essential oil was as low as 50%.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, its hydroxyl group hydrophilic head is directed outward to maintain water solubility (dos Santos et al, 2017). Numerous studies have successfully used β-cyclodextrins to encapsulate coriander essential oil (Silva et al, 2019), orange peel essential oil, eucalyptus essential oil (Kringel et al, 2017), cinnamon essential oil (Ahmed et al, 2022), and clove essential oil (Adjali et al, 2022)…”
Section: Cyclodextrinmentioning
confidence: 99%
“…In addition, its hydroxyl group hydrophilic head is directed outward to maintain water solubility (dos Santos et al, 2017). Numerous studies have successfully used β‐cyclodextrins to encapsulate coriander essential oil (Silva et al, 2019), orange peel essential oil, eucalyptus essential oil (Kringel et al, 2017), cinnamon essential oil (Ahmed et al, 2022), and clove essential oil (Adjali et al, 2022) to create a stable sustained release system. The majority of β‐cyclodextrin/essential oil encapsulation methods are used to solve the food preservation problem and lengthen the shelf life of food.…”
Section: Materials For Essential Oils Encapsulationmentioning
confidence: 99%